Views on Khiyar 'Aib Practices During the Covid-19 Pandemic: Case Pasar Raya Meulaboh - Febriani, Asra; Nurdin, Muhammad Riza; Yustinur, Nadia (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2024)
The problem in this study is the practice related to the buyer's right in terms of returning transaction goods in treading because of the damage in the object of trade (khiyar 'aib) practice and this occurred during  the Covid-19 pandemic which encouraged fraudulent actions in trade. The purpose of this research is to see the perspective of Sharia Economic Law on the practice of khiyar 'aib that occurred in Meulaboh Supermarket during the Covid-19 pandemic. The type of research that the author uses in this study is a type of qualitative research, in this study the author uses data collection techniques by combining two methods, namely literature research methods and field research methods.  In the literature research method, the author presents data based on three data sources namely primary data source, secondary data source and tertiary data source. While in the field research method, the author presents data based on observations, interviews and documentation studies which the author then analyzes in a descriptive way. Based on the results of the study, it can be concluded that the practice of khiyar 'aib in the Pasar Raya Meulaboh  continues to run in accordance with Sharia Economic Law both in terms of conditions, time limits, the abolition of khiyar 'aib and so on. The Covid-19 pandemic only affected the income of sellers at Meulaboh Supermarket, but did not affect the practices contained in it, especially the practice of khiyar 'aib. This research contributes to finding the practice of khiyar carried out by perpetrators of buying and selling transactions and presents it in the form of data where previously the practice of khiyar at Pasar Raya Meulaboh had never been exposed before even though this practice was carried out quite often. The author also identified that there were sellers and buyers who did not know that the practices they were carrying out were khiyar practices. This research also provides education to informants about the practice of khiyar that occurs among traders.